Menelaah Tabiat Industri Televisi Rating Sudah Jadi Tauhid - Khusairi, Abdullah (Universitas Islam Negeri Imam Bonjol Padang, 2012)
Rating program is the average viewer to program expressed as a percentage of the group sample or total potential. The rating point program is based on the smallest unit of time one minute. Rating required for television stations to measure the success of an event and is closely related to the success of advertisers rating to